2007
DOI: 10.1253/circj.71.1606
|View full text |Cite
|
Sign up to set email alerts
|

Association of Atrial Arrhythmia and Sinus Node Dysfunction in Patients With Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Statistical AnalysisAll numeric data are presented as the means ± SD. Because of differences in the variables and limited sample numbers, statistic analysis was performed using Wilcoxon nonparametric analysis or chi-square analysis when necessary. A p-value less than 0.05 was considered significant. Circ J 2007; 71: 1606 -1609 (Received May 8, 2007 revised manuscript received June 14, 2007; accepted June 22, 2007 Background This study was performed to investigate the frequency and importance of supraventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 24 publications
4
90
0
1
Order By: Relevance
“…In addition to ventricular arrhythmias, these patients also develop sinus node dysfunction and bradycardia, which frequently requires permanent pacemaker insertion. Computational studies further reinforce the idea that SAN dysfunction results from leaky RYR2-containing Ca 2+ stores (5). These studies emphasize the importance of Ca 2+ signaling in the automaticity of SANCs.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…In addition to ventricular arrhythmias, these patients also develop sinus node dysfunction and bradycardia, which frequently requires permanent pacemaker insertion. Computational studies further reinforce the idea that SAN dysfunction results from leaky RYR2-containing Ca 2+ stores (5). These studies emphasize the importance of Ca 2+ signaling in the automaticity of SANCs.…”
supporting
confidence: 69%
“…S4). Therefore, the reduction in I Ca-L may be due to the depletion of SR Ca 2+ stores in SANCs from cSTIM1 −/− mice, as has been described for SANCs harboring mutations in mouse RyR2 that cause CPVT (5,22,23). We also extended our investigation to include T-type Ca 2+ currents (I Ca-T ).…”
Section: Significancementioning
confidence: 71%
See 1 more Smart Citation
“…28,49,50 Indeed, CPVT patients may be at increased risk of inappropriate shocks due to CPVT-related supraventricular arrhythmias. 51,52 In 2008, the first three CPVT patients with successful prevention of adrenergically-mediated arrhythmias with left cardiac sympathic denervation (LCSD) were described, some with long-term follow-up. 53 After this, more successful experiences with LCSD in CPVT have been published.…”
Section: Reviewmentioning
confidence: 99%
“…52 As well as ventricular arrhythmias, patients with CPVT also show atrial arrhythmias and sinoatrial node dysfunction. 53 Work on isolated RyRs has shown that the probability that they are open at low cytoplasmic concentrations is greater than for wild-type RyRs. 54,55 It has also been shown that DADs are more likely to occur in cells that express either mutant RyRs or CSQ.…”
Section: Catecholaminergic Polymorphic Vt (Cpvt)mentioning
confidence: 99%